2022
DOI: 10.3390/ani12030320
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Microbiome Profile in Different Parts of the Intestine in Piglets with Diarrhea

Abstract: Determining the taxonomic composition of microbial consortia of the piglet intestine is of great importance for pig production. However, knowledge on the variety of the intestinal microbiome in newborn piglets is limited. Piglet diarrhea is a serious gastrointestinal disease with a high morbidity and mortality that causes great economic damage to the pig industry. In this study, we investigated the microbiome of various sections of the piglet intestine and compared the microbiome composition of healthy and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…Escherichia Shigella, Streptococcus, Sphaerochaeta and Enterococcus were increased in pigs with diarrhea compared to the healthy group. Surprisingly, the bacterial diversity was higher in the healthy pigs compared to pigs with diarrhea among all intestinal segments (illeum, caecum, colon and rectum) ( 112 ).…”
Section: Weaning Of Piglets and Diarrhea Occurrencementioning
confidence: 99%
“…Escherichia Shigella, Streptococcus, Sphaerochaeta and Enterococcus were increased in pigs with diarrhea compared to the healthy group. Surprisingly, the bacterial diversity was higher in the healthy pigs compared to pigs with diarrhea among all intestinal segments (illeum, caecum, colon and rectum) ( 112 ).…”
Section: Weaning Of Piglets and Diarrhea Occurrencementioning
confidence: 99%
“…Diarrhea is deemed as the major factor impeding the development of livestock industry because of it could cause reduced growth performance and a large number of deaths of farmed animals ( 18 , 19 ). Increasing surveys demonstrated that diarrhea occurs in almost all animals, causing huge economic losses every year ( 20 , 21 ). Diarrhea could cause the body to lose a great of water and nutrients, thus resulting in energy imbalances, weakness, starvation or even death ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The less abundant genera were Lactobacillus, Lachnoclostridium, Enterococcus, Alloprevotella and Peptostreptococcus . Although microbial profiles in piglets can differ depending on the circumstances, the abovementioned genera are frequently found as the normal microbiota in the early life stages of piglets ( 40 , 41 ). Although Escherichia are known as pathogens which can cause diseases in new-born piglets, their high prevalence in pigs does not indicate infection, as E. coli , which is the most prevalent species among Escherichia is highly variable and usually has no enterotoxigenic properties.…”
Section: Resultsmentioning
confidence: 99%